2021
DOI: 10.9734/afsj/2021/v20i930346
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Jackfruit (Artocarpus heterophyllus Lam)

Abstract: Background: Jackfruit (Artocarpus heterophyllus Lam) is widely cultivated in tropical and sub-tropical areas worldwide. The tree is highly productive, resilient, and requires minimal care. Jackfruit has a characteristic flavour and is highly versatile. Several studies report the importance of the tree and fruits, ranging from food and medicine to the provision of several value-added products. In spite of the many benefits the plant offers, it has not been sufficiently incorporated in the general food system, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 87 publications
0
1
0
Order By: Relevance
“…Buah nangka yang tumbuh tersebut yaitu varietas Kanaanansi, Namusaayi, Namata, dan Serebera (Nakintu et al, 2023). Buah nangka mengandung protein, mineral, lemak, karbohidrat, serat dan energi yang jumlahnya berbeda tergantung tingkat kematangannya (Nansereko & Muyonga, 2021). Nangka juga mengandung air yang cukup tinggi, sehingga buah nangka memiliki umur simpan yang relative singkat.…”
Section: Pendahuluanunclassified
“…Buah nangka yang tumbuh tersebut yaitu varietas Kanaanansi, Namusaayi, Namata, dan Serebera (Nakintu et al, 2023). Buah nangka mengandung protein, mineral, lemak, karbohidrat, serat dan energi yang jumlahnya berbeda tergantung tingkat kematangannya (Nansereko & Muyonga, 2021). Nangka juga mengandung air yang cukup tinggi, sehingga buah nangka memiliki umur simpan yang relative singkat.…”
Section: Pendahuluanunclassified
“…Simple processing techniques are recommended to overcome the current obstacles and develop nutritious, easily accessible, long-lasting food products (Ranasinghe, Maduwanthi, and Marapana 2019). Previous literature demonstrated that the fruit is suitable for being processed into various products such as jackfruit chips, wine, jam, or jackfruit-nut-bars (Nansereko and Muyonga 2021;Xing, Keding, and Pawelzik 2021).…”
Section: Introductionmentioning
confidence: 99%